2021
DOI: 10.1186/s13018-021-02562-8
|View full text |Cite
|
Sign up to set email alerts
|

Surgical outcomes and risk factors for poor outcomes in patients with cervical spine metastasis: a prospective study

Abstract: Background Few studies have addressed the impact of palliative surgery for cervical spine metastasis on patients’ performance status (PS) and quality of life (QOL). We investigated the surgical outcomes of patients with cervical spine metastasis and the risk factors for a poor outcome with a focus on the PS and QOL. Methods We prospectively analyzed patients with cervical spine metastasis who underwent palliative surgery from 2013 to 2018. The East… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 28 publications
(53 reference statements)
0
10
0
Order By: Relevance
“…Spinal cord decompression via tumor laminectomy renders the affected segments of the spine less stable, promoting sagittal malalignment such as post-laminectomy kyphosis that is associated not only with pain, but also with neurological deterioration. This particularly holds true for junctional segments, where often not only posterior, but also anterior column stabilization may be warranted [24,25].…”
Section: Instrumentation For Spinal Stabilization In Patients With Ac...mentioning
confidence: 99%
“…Spinal cord decompression via tumor laminectomy renders the affected segments of the spine less stable, promoting sagittal malalignment such as post-laminectomy kyphosis that is associated not only with pain, but also with neurological deterioration. This particularly holds true for junctional segments, where often not only posterior, but also anterior column stabilization may be warranted [24,25].…”
Section: Instrumentation For Spinal Stabilization In Patients With Ac...mentioning
confidence: 99%
“…The CTJ is a biomechanically challenging region for spinal surgery and one of the major risk factors for poor surgical outcomes in MCSTs [ 8 , 10 - 13 ]. Interestingly, although the 5.5-mm rod group had significantly more lesions located at the CTJ—a region more unstable than C3–6—with a higher mean SINS than the 3.5-mm rod group, the postoperative collapse rate was significantly lower in the 5.5-mm rod group than in the 3.5-mm rod group [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…The cervicothoracic junction (CTJ), where approximately 10% of all spinal metastases occur, is the most challenging anatomical transitional area for treating spinal pathologies [ 8 , 10 - 13 ]. Although controversial, the consensus of surgical treatment has consistently improved biomechanical stability [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…As an advanced stage of cancer, metastatic spinal disease is often characterized by severe back pain, infection, neurological sequelae, and ambulatory disability (8), which are particularly challenging for surgeons. Of note, patients with spine metastasis have been proved to be relevant to declined life expectancy (8) and poor quality of life (10)(11)(12) because of above complications. Studies have demonstrated that surgical interventions could be capable of improving the quality of patient's remaining life due to immediate pain relief and functional recovery among patients with spine metastasis (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…Of note, patients with spine metastasis have been proved to be relevant to declined life expectancy (8) and poor quality of life (10)(11)(12) because of above complications. Studies have demonstrated that surgical interventions could be capable of improving the quality of patient's remaining life due to immediate pain relief and functional recovery among patients with spine metastasis (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%